Worldwide regional variations in home advantage in association football - Pollard, R. (Journal of Sports Sciences, 2006)
Home advantage plays an important part in determining the result of a game of football. Its existence and magnitude is well documented in England, but its causes are still not completely understood. In this study, reliable estimates of home advantage are calculated for the domestic leagues of all countries of Europe and South America, as well as a selection of countries from other continents. The results of all games during the last six seasons are used for each of these 72 countries. In Europe, home advantage in the Balkan countries, especially Bosnia and Albania, is much higher than average. It is generally lower than average in northern Europe, from the Baltic republics, through Scandinavia to the British Isles. In South America, home advantage is high in the Andean countries and lower elsewhere, especially in Uruguay. Home advantage is not unusually high or low in any of the countries from other continents. A multiple regression model for the 51 European countries, which included variables for geographical location, crowd effects and travel, accounted for 76.7% of the variability in home advantage. The large geographical variations can be interpreted in terms of territoriality being a contributing factor to home advantage.